2017
DOI: 10.3727/096504017x14876245096439
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic Variations Associated With Doxorubicin-Induced Cardiotoxicity in Breast Cancer Patients

Abstract: Doxorubicin (DOX) is a commonly used antineoplastic agent for the treatment of various malignancies, and its use is associated with unpredictable cardiotoxicity. Susceptibility to DOX cardiotoxicity is largely patient dependent, suggesting genetic predisposition. We have previously found that individual sensitivity to DOX cardiotoxicity was associated with differential expression of genes implicated in inflammatory response and immune trafficking, which was consistent with the increasing number of reports high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 25 publications
(19 reference statements)
2
36
0
Order By: Relevance
“…7 The analysis and comparison of the genotype distribution of breast cancer patients who developed abnormal LVEF decline after DOX-based chemotherapy and patients who did not identified genetic variability in several human leukocyte antigen (HLA) genes as potential candidates for association with DOX cardiotoxicity. 8 The later finding is consistent with reports showing the presence of susceptibility loci within the HLA gene region for several inflammatory and autoimmune diseases, 9 between chemotherapy, and development of autoimmune and rheumatic features in cancer patients. 10 Proteins in blood that represent the inflammation status or a drug-induced immunological response potentially could be early biomarkers of drug-induced cardiotoxicity.…”
Section: Impact Statementsupporting
confidence: 88%
“…7 The analysis and comparison of the genotype distribution of breast cancer patients who developed abnormal LVEF decline after DOX-based chemotherapy and patients who did not identified genetic variability in several human leukocyte antigen (HLA) genes as potential candidates for association with DOX cardiotoxicity. 8 The later finding is consistent with reports showing the presence of susceptibility loci within the HLA gene region for several inflammatory and autoimmune diseases, 9 between chemotherapy, and development of autoimmune and rheumatic features in cancer patients. 10 Proteins in blood that represent the inflammation status or a drug-induced immunological response potentially could be early biomarkers of drug-induced cardiotoxicity.…”
Section: Impact Statementsupporting
confidence: 88%
“…The obtained results shown in Figure 12, indicated the negligible cytotoxicity of the PEG1500-PMNPs in incubation intervals of 24, 48, and 72 h. In contrast, incubation of A549 cells with free DOX led to 28%, 53%, and 89% reduction of the cell viability after 24, 48, and 72 h, respectively. Although the concentration of free DOX applied in this study was significantly higher than its half maximal inhibitory concentration (IC50), a relatively low cytotoxicity was observed at the initial 24 h, probably due to the genetic polymorphism, which its manifestation in the used A549 cell lines may translate to reduced transportation rates of free DOX [38,39]. However, the obtained results aptly indicated the significant cytotoxicity of free DOX at increased intervals, where the cell viability ratio reached approximately 10% after 72 h. In contrast, when the DOX-PEG1500-PMNPs were added, the cell viability was reduced to 20%, 25%, and 28% for incubation intervals of 24, 48, and 72 h, which again indicated the rapid partial leakage of the encapsulated DOX within the medium.…”
Section: Cytotoxicity Assaysmentioning
confidence: 79%
“… 12 , 13 Vulnerability to doxorubicin cardiotoxicity is largely patient dependent, suggesting genetic predisposition, and some studies found that this condition was associated with dysregulation of genes implicated both in inflammation and autoimmune disorders. 14 …”
Section: Discussionmentioning
confidence: 99%